Love is a story : a new theory of relationships - Sternberg, Robert J. (Oxford University Press, 1998)
In this groundbreaking work, Robert Sternberg opens the book of love and shows you how to discover your own story--and how to read your relationships in a whole new light. What draws us so strongly to some people and repels us from others? What makes some relationships work so smoothly and others burst into flames? Sternberg gives us new answers to these questions by showing that the kind of relationship we create depends on the kind of love stories we carry inside us. Drawing on extensive research and fascinating examples of real couples, Sternberg identifies 26 types of love story--including.